2021
DOI: 10.1002/cnr2.1561
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of caspase‐3 and gasdermin E and their involvement in the occurrence and prognosis of lung cancer

Abstract: BackgroundPyroptosis plays a dual role in the development of cancer and malignancy, and as such, may potentially be a new target for cancer treatment. However, the in ammatory response to pyroptosis may have adverse effects on the body. The roles of gasdermin E (GSDME), caspases, and related proteins associated with pyroptosis in cancer remain controversial. This study aimed to explore whether the expression levels of caspase-3 and GSDME affect the clinical stage, pathological grade, and survival prognosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In lung cancer, the balance between cell death and cell division is disrupted, leading to the uncontrolled growth and proliferation of cancer cells. Research has shown that the levels of caspase-9 are often decreased in lung cancer cells, which may contribute to the resistance of these cells to apoptosis (Huang et al 2022;Li et al 2022). BaP induced lung cancer mice exhibited suppressed level of caspase-3 and caspase-9 and metformin and atorvastatin combination treatment remarkably restored the level.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, the balance between cell death and cell division is disrupted, leading to the uncontrolled growth and proliferation of cancer cells. Research has shown that the levels of caspase-9 are often decreased in lung cancer cells, which may contribute to the resistance of these cells to apoptosis (Huang et al 2022;Li et al 2022). BaP induced lung cancer mice exhibited suppressed level of caspase-3 and caspase-9 and metformin and atorvastatin combination treatment remarkably restored the level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that both N-GSDME and N-GSDMD can augment caspase 3/7-mediated apoptotic cell death in cancer cells by promoting release of proapoptotic proteins like cytochrome C from mitochondria 108 . GSDMD has also been shown to target mitochondria following intracellular LPS-dependent activation of caspase 11 in endothelial cells 129 . In this context, N-GSDMD promotes mtDNA release and cGAS/STING activation in the absence of cell death, suggesting that redistribution of GSDMD to and from the mitochondria may constitute an important node in regulating cell death outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…GSDME, caspase 3, and caspase 8 are more abundantly expressed in tumor tissue. Elevated GSDME expression is associated with a higher postoperative survival rate and a lower lymph node metastasis rate, which suggests that it may serve as a predictor of prognosis in lung cancer patients 124 . LUAD prognosis is also associated with new pyroptosis‐related prognostic markers, including NOD1, NLRP1, NLRP2, NLRP7, and caspase 6.…”
Section: Pyroptosis and Inflammasomes In Cancermentioning
confidence: 99%
“…Elevated GSDME expression is associated with a higher postoperative survival rate and a lower lymph node metastasis rate, which suggests that it may serve as a predictor of prognosis in lung cancer patients. 124 LUAD prognosis is also associated with new pyroptosis‐related prognostic markers, including NOD1, NLRP1, NLRP2, NLRP7, and caspase 6. The notion that pyroptosis can mediate the TME to exert an antitumor effect is supported by these genes, which are intimately linked to immune infiltration.…”
Section: Pyroptosis and Inflammasomes In Cancermentioning
confidence: 99%